2010
DOI: 10.1068/p6543
|View full text |Cite
|
Sign up to set email alerts
|

Estimating Aggression from Emotionally Neutral Faces: Which Facial Cues are Diagnostic?

Abstract: The facial width-to-height ratio, a size-independent sexually dimorphic property of the human face, is correlated with aggressive behaviour in men. Furthermore, observers' estimates of aggression from emotionally neutral faces are accurate and are highly correlated with the facial width-to-height ratio. We investigated whether observers use the facial width-to-height ratio to estimate propensity for aggression. In experiments 1a-1c, estimates of aggression remained accurate when faces were blurred or cropped, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
80
0
1

Year Published

2011
2011
2018
2018

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 80 publications
(90 citation statements)
references
References 52 publications
9
80
0
1
Order By: Relevance
“…Indeed, individuals are more likely to follow the gaze of masculine faced men and women compared to feminine faced individuals (Jones et al, 2010). In line with these ideas, and with the findings that this ratio in CEO's predicts company profits, the facial width-to-height ratio have been associated with perceived aggression, trait dominance using questionnaires, and aggression in a naturalistic setting (Carre and McCormick, 2008;Carre et al, 2009;Carre et al, 2010).…”
Section: Understanding Why Appearance Matterssupporting
confidence: 64%
“…Indeed, individuals are more likely to follow the gaze of masculine faced men and women compared to feminine faced individuals (Jones et al, 2010). In line with these ideas, and with the findings that this ratio in CEO's predicts company profits, the facial width-to-height ratio have been associated with perceived aggression, trait dominance using questionnaires, and aggression in a naturalistic setting (Carre and McCormick, 2008;Carre et al, 2009;Carre et al, 2010).…”
Section: Understanding Why Appearance Matterssupporting
confidence: 64%
“…Recent research (e.g. [13,28]) has demonstrated that observers view men's facial WHR as a signal of aggression and untrustworthiness, and adjust their behaviour as a result of these perceptions. If, for instance, observers respond to facial cues by deferring to men whom they perceive to be aggressive based on their facial WHR, these men may find it easier to take advantage of others.…”
Section: Discussionmentioning
confidence: 99%
“…The ratings of aggression were found to be correlated with both the participant's face ratio and the participant's aggression during the PSAP. Additionally, the association between the face ratio and estimates of aggression persisted even when the same stimuli were displayed for as little as 39 ms [9], blurred (to prevent judgements based on individual facial features [15]) or cropped (to maintain the face ratio yet remove influence of forehead, chin, and ears [15]). In another study, adult and 8-year-old White (from Canada) and Asian (from China) observers judged aggression in same- and other- race male faces (White and Asian faces [16]).…”
Section: Introductionmentioning
confidence: 99%